Media portrayals of mental health: analysing stigma, stereotypes and advocacy narratives - Shuyuan, Luo (Journal of the Belarusian State University. Journalism, 2025)
This article examines how Chinese media represents mental health issues and impact of this representation on public perception, particularly the formation of stigma and stereotypes. The study examines mainstream news media, film and television works, social media platforms. It is found that Chinese media frequently links mental illness to violence and instability, reinforcing public discrimination and fear. Advocacy narratives, however, help dismantle stereotypes and reduce stigma.
Keywords: media representation; mental health issues; stigmatisation; stereotype; advocacy narratives; mental health; cognition; Chinese media